Brasstacks and Beyond : Perception and Management of Crisis in South Asia - Bajpai, Kanti P.; [et al.] (GHQ, Rawalpindi Army Education Press, 2000)
With special reference to Brasstacks-related crisis between India and Pakistan.
Include Table, Note and Index
Keywords: India -- Politics and government -- Pakistan -- Diplomatic relations